2019
DOI: 10.1128/mbio.01822-19
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Emergence of Mismatch Repair Deficiency Facilitates Rapid Evolution of Ceftazidime-Avibactam Resistance in Pseudomonas aeruginosa Acute Infection

Abstract: Strains of Pseudomonas aeruginosa with deficiencies in DNA mismatch repair have been studied in the context of chronic infection, where elevated mutational rates (“hypermutation”) may facilitate the acquisition of antimicrobial resistance. Whether P. aeruginosa hypermutation can also play an adaptive role in the more dynamic context of acute infection remains unclear. In this work, we demonstrate that evolved mismatch repair deficiencies may be exploited by P. aeruginosa to facilitate rapid acquisition of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 78 publications
(95 reference statements)
2
33
0
Order By: Relevance
“…Finally, several recent research studies on non-CF infections reported that P. aeruginosa adaptive mechanisms occur at the very beginning of the colonization, emphasizing the underappreciated role of genetic adaptation in acute infections [51, 58, 59]. Altogether, these results indicate that different modes of selection arise with time, according to infection stage and severity.…”
Section: Genomic Adaptation Of P Aeruginosamentioning
confidence: 83%
See 2 more Smart Citations
“…Finally, several recent research studies on non-CF infections reported that P. aeruginosa adaptive mechanisms occur at the very beginning of the colonization, emphasizing the underappreciated role of genetic adaptation in acute infections [51, 58, 59]. Altogether, these results indicate that different modes of selection arise with time, according to infection stage and severity.…”
Section: Genomic Adaptation Of P Aeruginosamentioning
confidence: 83%
“…Indeed, it has been shown that antibiotic exposure promotes the emergence of hypermutability in P. aeruginosa, then favouring acquisition of antibiotic resistance [45,[48][49][50][51]. However, Mehta and colleagues also observed that some hypermutable lineages would spontaneously decline and disappear from the evolving population [49].…”
Section: Hypermutabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This is evident in clinical populations in bacterial species such as Pseudomonas aeruginosa, Burkholderia cepacia, Staphylococcus aureus and Salmonella enterica, in which mutator strains are significantly more resistant to antibiotics than non-mutator strains [49,54,56,57,61,[85][86][87]. Serial whole genome sequencing of P. aeruginosa isolates from a patient, in whom clonal ceftazidime-avibactam (CZA) resistance emerged over the course of days, showed a lack of MMR which facilitated the rapid evolution of resistance during acute infection [87]. In vitro adaptive evolution experiments with a mutS strain also showed rapid acquisition of CZA resistance in vitro [87].…”
Section: A Mutator Phenotype Is Associated With Increased Resistance ...mentioning
confidence: 99%
“…Mutators are a potential concern for combination therapy, as multi-resistance is often found in mutator lineages, although this is believed to have arisen due to sequential application of monotherapy 22,[28][29][30][31] . Direct evidence for the efficacy of combinations against mutators is mixed [32][33][34] . We imposed selection for resistance by increasing the concentrations of antibiotics over a physiologically-relevant concentration gradient 35,36 .…”
Section: Introductionmentioning
confidence: 99%